Hereditary multiple exostoses - a rare case - Dr. Shivaprakash. N.C; Dr Naveen K S; Dr. Sowmya.S (Pediatric Review: International Journal of Pediatric Research, 2017)
Hereditary Multiple Exostoses (HME) is a genetically transmitted bone dysplasia that is inherited in an autosomal dominant manner. It usually presents after the age of two years as multiple bony growths on the appendicular skeleton. It is a rare condition with incidence of 0.9-2/1,00,00 with few reported cases. We are hereby reporting an 8 year old boy with typical clinical and radiological features of Hereditary Multiple Exostoses (HME) in our hospital.